Beyond Traditional Models: Integrating EUCS, SERVQUAL, and UEQ in SeaBank - Raihana Nabilatulrahmah; Dinda Lestarini; Iin Seprina; Ari Wedhasmara; Dinna Yunika Hardiyanti (Universitas Hamzanwadi, 2026)
Research on digital banking satisfaction remains conceptually fragmented, as End-User Computing Satisfaction (EUCS), SERVQUAL, and User Experience Questionnaire (UEQ) reflect distinct evaluative paradigms that often produce inconsistent results when applied independently. This study develops and validates an integrated model capturing informational, service, system, and experiential determinants of satisfaction in a branchless digital banking context. Data from 212 active SeaBank users were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a Two-Stage approach. The model explains 76.5% of the variance in user satisfaction. User experience is the strongest predictor, followed by system quality and information quality, while service quality is not statistically significant. The findings indicate an experience-centric evaluation structure, where affective and system-related factors outweigh traditional service dimensions. This study provides a unified empirical validation of EUCS, SERVQUAL, and UEQ, clarifying their hierarchical relationships and indicating the reduced relevance of service quality in fully digital environments. Practically, the results highlight the importance of UI/UX optimization, system reliability, and experiential design for enhancing user retention. The Gen Z-dominated sample and cross-sectional design limit broader generalization, suggesting the need for longitudinal and cross-context validation.